Insights and Considerations for “Higher Intraocular Levels of Inflammatory Factors are Related to Retinal Vascular and Neurodegeneration in Myopic Retinopathy” [Letter] - Cao H; Ma X (Journal of Inflammation Research)
Haixing Cao, Xiang Ma Department of Ophthalmology, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning Province, People’s Republic of ChinaCorrespondence: Xiang Ma, Department of Ophthalmology, the First Affiliated Hospital of Dalian Medical University, 222 Zhongshan Road, Dalian, Liaoning Province, People’s Republic of China, Tel +8618098876399, Email xma9467@vip.sina.com